PENGENDALIAN KUALITAS PROSES PRODUKSI PAKAN IKAN DENGAN MENERAPKAN QUALITY CONTROL PRODUKSI (QCP) DI PT CENTRAL PERTIWI BAHARI - Putri Endah Suwarni (Industrika : Jurnal Ilmiah Teknik Industri, 2018)
The research method used is P-Chart method, with diagram of upper and lower control chart, check sheet, pareto diagram, and cause and effect diagram. The result of analysis using Pareto Diagram can be seen that from 199,880 kg or 0.6097% defective product, it is dominant defect 0.4282% in Size, 0.0981% in Floating, 0.0633% in Moisture, 0.0150% in Belang, and Others 0.0051%. Occurrence of fish feeds product defect caused by material factors, machine, methods, and man. Based on these factors that affect the quality of fish feeds are lack of training and lack of skill, exhaustion and negligence, lack of socialization of SOP (Standard Operating Procedures) and techniques in improper mixing, poor quality materials and material storage is too long , decreased machine productivity and lack of maintenance or maintenance of machinery. Application of quality control of fish feed production process at PT Central Pertiwi Bahari has been running well, this is proved by the percentage of major defect that does not exceed the maximum standards specified by the company. Keywords: quality control, check sheet, pareto diagram, cause-effect diagram, control chart (p-chart).